PREPARATION of [BzMe3N]2[Na2W4O12(OMe)4(MeOH)6].6MeOH - Bakri, Ridla (UI Scholars Hub, 2003)
An attempt to prepare trinuclear tungsten oxoalkoxides [BzMe3N]3 [W3O8 (OMe)5 ] from the reaction between WO2 (OMe)2 , [BzMe3N]2WO4 and [BzMe3N](OMe) in the ratio of 2:1:1 in MeOH produced [BzMe3N]2 [Na2W4O12(OMe)4 (MeOH)6 ].6MeOH. Suitable crystals for X-ray chrystallographic studies were obtained from hot mixture of methanol-acetonitrile solution. The I.R., 1H-NMR, and microanalysis data including crystal structure of [Na2W4O12(OMe)4 (MeOH)6 ] 2- anion are reported